Fiqh siyasah dalam Penerapan Demokrasi di Indonesia - Nurokhman, Nurokhman; Mulyani, Nisa Putri (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2021)
Democracy is a form of two words demos (the people) and cratein or cratos (power and sovereignty). The combination of the words demos and cratein or cratos forms the word democracy which has a general understanding as a form of government of the people (government of the people) in which the highest power lies in the hands of the people carried out directly by the people or through their representatives through direct and indirect election mechanisms. freely. For this study, the authors used qualitative data. In a systematic and standard procedure to obtain the required data there is always a relationship between the data collection method and the research problem to be solved, the data collection method used in this research is the study method or (library). Democratic ethics can simply be understood as a political ethic that adheres to the existential principles of democracy. Democratic ethics is part of political ethics that places democracy as an ethical measuring tool. If political ethics questions the legitimacy factor that is the basis of power, while political ethics emphasizes more on how to do politics. The problem of the way, the making, or the behavior to express the attitude of political action by referring to the elements of democratic values ​​is what is referred to as democratic political ethics. So the ethics of democracy is a democratic way of doing politics. What is the democratic way of doing politics? Theoretically, democratic ethics is a moral teaching in acting that prioritizes the will of the people through equal respect for the rights to be able to freely express choices and opinions. Abstrak Demokrasi berasal dari dua kata yaitu demos (rakyat) dan cratein atau cratos (kekuasaan dan kedaulatan). Gabungan kata demos dan cratein atau cratos membentuk kata demokrasi yang mempunyai pengertian umum sebagai bentuk pemerintahan dari rakyat (government of people) dimana kekuasaan tertinggi berada di tangan rakyat yang dilaksanakan langsung oleh rakyat. atau melalui perwakilannya melalui mekanisme pemilihan langsung. dengan bebas. Untuk penelitian ini, penulis menggunakan data kualitatif. Dalam suatu prosedur yang sistematis dan baku untuk memperoleh data yang dibutuhkan selalu ada hubungan antara metode pengumpulan data dengan masalah penelitian yang akan dipecahkan, metode pengumpulan data yang digunakan dalam penelitian ini adalah metode studi atau (perpustakaan). Etika demokrasi secara sederhana dapat dipahami sebagai etika politik yang menganut prinsip-prinsip eksistensial demokrasi. Etika demokrasi merupakan bagian dari etika politik yang menempatkan demokrasi sebagai alat ukur etis. Jika etika politik mempersoalkan faktor legitimasi yang menjadi dasar kekuasaan, sedangkan etika politik lebih menekankan pada bagaimana berpolitik. Masalah cara, pembuatan, atau perilaku untuk mengungkapkan sikap tindakan politik dengan mengacu pada unsur-unsur nilai demokrasi inilah yang disebut dengan etika politik demokrasi. Jadi etika demokrasi adalah cara berdemokrasi dalam berpolitik. Bagaimana cara demokrasi dalam berpolitik? Secara teoritis, etika demokrasi adalah ajaran moral dalam bertindak yang mengutamakan kehendak rakyat melalui penghormatan yang sama terhadap hak untuk dapat bebas berekspresi. pilihan dan pendapat.